Purification and properties of codeinone reductase (NADPH)from Papaver somniferum cell cultures and differentiated plants - LENZ, R.; ZENK, M.H.
Codeinone reductase (NADPH), which catalyzes the stereospecific reduction of (-)codeinone to (-)codeine, was detected and purified to electrophoretic homogeneity from a cytosolic fraction of Papaver sonziziferuin L. cell cultures. The purification involved ammonium sulfate precipitation (40- 80
Keywords: CODEINE; MORPHINE; CODEINONE REDUCTASE; PUPAVER; CELL CULTURE